Przewinienia hudūd w klasycznym prawie karnym muzułmańskim - zarys tematyki - Sadowa, Katarzyna (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
The subject of the article is the introduction to the issue of basic category of crimes established directly in the Quran – hudūd crimes. Firstly author shortly characterizes main features of classic Muslim criminal law, further analyzes each of hudūd crimes, which are: Sariqa –theft; Hirāba/ qat‘al-tar’iq – banditry; Zinā – unlawful sexual intercourse,; Qadhf – an unfounded accusation of unlawful sexual intercourse (slander, calumny, defamation); Shurb khamr – the drinking of alcohol; Ridda – apostasy; Baghi– armed uprising against the ruler
Keywords: islam; prawo muzułmańskie; prawo karne muzułmańskie; Koran; hudūd